From Byzantium to the Early Greek Enlightenment : Books, Writers, and Ideologies in Early Modern Greek Contexts (Late 15th − Early 18th Centuries) - Roilos, Panagiotis, (Brill's Studies in Intellectual History ;, 2026)
This book explores early modern Greek literary and wider cultural production and its connections with different traditions and sociocultural or political networks in the multicultural milieus where it emerged and circulated, especially in parts of the Greek world under Venetian and Ottoman rules, or in major centers of the Greek diaspora across Western Europe. Particular emphasis is placed on scholarly debates about issues of historical and cultural continuities and discontinuities; the transition from manuscript production and circulation to print networks; and the negotiation of ethnic and cultural ideologies and broader mentalities as articulated in representative, but not necessarily 'canonical,' works of the period.